Influence of Product Quality, Price Perception, and Lifestyle on Purchasing Decisions of Uwinfly Brand Electric Motorcycles in Semarang City - Meilina Dyah Setyani; Sugiyanta; Ana Putri Nastiti (Politeknik Negeri Semarang, 2025)
This study looks at how much electric motorcycles are being used in Indonesia, with a focus on the Uwinfly brand in Semarang City. The goal is to understand how product quality, how people see the price, and their lifestyle affect their decision to buy. The research uses a survey with 100 people, chosen through non-probability and purposive sampling methods. The findings show that product quality and price perception have a strong effect on buying decisions, but lifestyle does not. When all three factors are considered together, they all have a significant impact. The study also found that about 50.6% of buying choices are influenced by these three factors, while the other 49.4% are affected by things not covered in this research.